RIGHTS AND POLICIES FOR WOMEN TO BE PROTECTED FROM SEXUAL VIOLENCE IN OBTAINING EDUCATION AT UNIVERSITIES - Carissa Dwilanisusantya; Ratih Widowati; Ifah Atur Kurniati (Faculty of Law Sriwijaya University, 2025)
Based on data from the National Commission on Violence Against Women in 2020, of the total cases of violence in the educational environment, 88% were cases of sexual violence. Higher education is the level of education with the highest percentage of sexual violence incidents, namely 35%. Women are the gender that is more often the victim of sexual violence, while based on human rights, women and men should have equal opportunities to get an education. To provide equal educational opportunities, Regulation of the Ministry of Edication, Culture, Research, and Technology of Indonesia (Permendikbudristek) number 30 of 2021 has been formed which regulates the prevention and handling of sexual violence, called PPKS in the higher education environment with the implementation of the formation of the PPKS Task Force (Satgas PPKS). However, this does not directly eliminate cases of sexual violence that occur in universities, in fact, until now there are still cases of sexual violence in various universities. Women are still easy targets for sexual violence. This study aims to identify the causes and problems of sexual violence against women and how to create appropriate policies in the educational environment so that it is safe and comfortable so that women no longer have a sense of worry. This study uses qualitative research methods to gain an in-depth and comprehensive understanding of acts of sexual violence and the formulation of appropriate policies in certain higher education environments related to the creation of a safe and comfortable educational environment.